OBTAINING HALAL CERTIFICATE FOR PROCESSED ANIMAL FOOD IN GARUT REGENCY IS CONNECTED WITH THE REQUIREMENTS OF HALAL ABATTOIR ACCORDING TO THE REGULATION OF THE MINISTER OF AGRICULTURE OF THE REPUBLIC OF INDONESIA - Sumiati, Yeti; Ramli, Tatty A.; Hendar, Jejen; Ayu, Hilmi; Rahayu, M. Dwivo; Shidiq, Rais M. (International Journal of Research -GRANTHAALAYAH, 2019)
Skin crackers are foods whose raw materials come from animals. As one of the leading culinary products in Garut Regency, the production of Sukaregang skin crackers is the result of people's economic activities that contribute to improving economic prosperity. Law No. 33 of 2014 concerning Halal Product Guarantee will be effective in 2019, where halal products are required to have a halal certificate, before including the halal label on the packaging. The purpose of this article is to analyze the acquisition of processed animal skin certificates in Garut Regency from the perspective of the Minister of Agriculture's regulation. The conclusion of this article is that Halal products must meet the halal and thayyib requirements. Products whose raw materials come from processed animals must come from Halal Certified Abattoirs, raw materials for Sukaregang skin crackers originating from leather supplied from Abattoirs that have no evidence that these raw materials are sourced from halal certified abattoirs, so 2019 targets are difficult to meet and will affect the people's economy. In Indonesia, there are still few Slaughterhouses that have been halal certified, as well as in Garut Regency there are no Halal Slaughterhouses that are certified.